2006
DOI: 10.1007/s11332-006-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foot support in rugby players: a baropodometric analysis

Abstract: Intense sports practice has effects on normal locomotion which may predispose athletes to certain injuries. The aim of the study was to evaluate weather playing rugby can change the distribution of forces on the surface of the foot plantar region and if these possible changes are caused by the high loading and the postural stances that this sport involves. The evaluation was performed using a baropodometer in static and dynamic conditions. We studied a group of 23 professional rugby players (scrums and threequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…The board contains 4800 platinum electronic sensors covered by an alveolar rubber captor, which sends pressure information from each foot to a computer. During the test, subjects stood on the platform in an orthostatic position for 10 seconds, as in the study of Ripani et al (20). The support surfaces of both feet and the percentage distribution of load in rearfoot and forefoot regions were evaluated.…”
Section: Baropodometric Examinationmentioning
confidence: 99%
“…The board contains 4800 platinum electronic sensors covered by an alveolar rubber captor, which sends pressure information from each foot to a computer. During the test, subjects stood on the platform in an orthostatic position for 10 seconds, as in the study of Ripani et al (20). The support surfaces of both feet and the percentage distribution of load in rearfoot and forefoot regions were evaluated.…”
Section: Baropodometric Examinationmentioning
confidence: 99%
“…5 , 12 Ripani et al believed that the demands of rugby being faster with more attacking and collisions could attribute to higher risk for injury by the number eight players. 2 Brooks and Kemp reported that tackling and scrimmaging by the loose-head prop could account for more injuries in the neck region in players in this position. 6 The scrum-half reported more injuries in the lumbar spine sustained from passing the ball.…”
Section: Discussionmentioning
confidence: 97%
“…Rugby players tend to adopt an unbalanced posture posteriorly resulting in difficulty in controlling foot stability resulting in a high prevalence of lower limb specifically ankle injuries. 2 , 3 The control of static and dynamic balance requires a complex interplay between proprioceptive, vestibular and visual factors. Body load data revealed that high levels of gravitational force are sustained in tackling and scrum tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ripani ve arkadaşları 23 profesyonel rugby oyuncusu ve 17 sağlıklı kişi üzerinde yaptıkları baropodometrik analizlerde, rugby oyuncularının sağlıklı kişilerle karşılaştırıldığında her iki ayak basınç alanı önemli derecede daha yüksek çıktığını açıklamışlardır (28). EMED-SF (Novel GmbH, Münih, Almanya) plantar basınç analiz sistemi kullanılarak yapılan benzer çalışmalarda ise 25 profesyonel basketbolcu ve kontrol grubu olarak 25 erkek gönüllü katıldığı, basketbolun ayak tabanı üzerine etkisinin araştırıldığı çalışmada sağ-sol ayak zirve basınç karşılaştırmasında basketbolcularda sağ ayak 1. metatars başı ve başparmağı küçük çıkarken, sağ ayak 4. metatars başı kontrol grubundan daha fazla olduğunu belirtilmiştir (29).…”
Section: Discussionunclassified